ΚΟΡΒΝ, Ο ΕΣΤΙΝ ΔωΡΟΝ - Duncan, J. (New Testament studies, 1970)
It is said that Jesus’ comments (Matt. xv. 4_6, Mark vii. 9_13) are unfair, or incompetently reported.2 It is desirable to clarify the practice and the law to which he referred.